Enhancing the Controller Design skills in the course Linear Control Systems - Kittur, Javeed (Journal of Engineering Education Transformations, 2018)
Controller design is very essential and critical in any control systems. In order to make a system function as desired it is required to design the controller parameters appropriately and then use it in the control system. In this paper an attempt is made in enhancing the controller design skills through assignments which involves design of controller parameters and its verification using simulation. Proportional - Integral (PI) controllers and Proportional - Integral - Derivative (PID) controllers are considered in the assignment questions. Zeigler - Nichols tuning method is used to design the controller parameters and these controller parameters are plugged in the controller and the system as a whole is simulated in SCILAB simulation tool for the verification of the controller design. The assessment of the assignment questions is done using rubrics. The result of assessment shows a good percentage attainment of the design outcome.